The ethnically diverse workplace : experience of immigrant Indian professionals in Australia - Gowan, Sunaina (Emerald Publishing Limited, 2023)
The Australian workplace continues to become more ethnically diverse as multiculturalism becomes a lived reality on a substantial scale. This change makes it vital to understand exclusionary or discriminatory practices and a detailed investigation of the potential relationship between work stress, acculturation, and its impact on emotional labour for minority group members has not been well researched. The Ethnically Diverse Workplace: Experience of Immigrant Indian Professionals in Australia documents the perceptions and experiences of exclusion after inclusion by Indian immigrants, particularly professionals. Many of the reports of discriminatory practices towards Indian immigrants or their stigmatisation based on accent, skin tone or national origin are anecdotal in nature and this book will seek to explain such practices and their impacts on the Indian immigrant community. The Ethnically Diverse Workplace works to encourage and promote greater awareness and understanding so that immigrant Indian professionals maybe better understood and served in Australia.